2021
DOI: 10.1038/s41467-021-24743-z
|View full text |Cite|
|
Sign up to set email alerts
|

Massively parallel in vivo CRISPR screening identifies RNF20/40 as epigenetic regulators of cardiomyocyte maturation

Abstract: The forward genetic screen is a powerful, unbiased method to gain insights into biological processes, yet this approach has infrequently been used in vivo in mammals because of high resource demands. Here, we use in vivo somatic Cas9 mutagenesis to perform an in vivo forward genetic screen in mice to identify regulators of cardiomyocyte (CM) maturation, the coordinated changes in phenotype and gene expression that occur in neonatal CMs. We discover and validate a number of transcriptional regulators of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…The functions and gene targets of GATA6 are partially redundant with GATA4 35 37 . To determine whether ERRγ and GATA6 also shared targets, we conducted an intersection analysis with GATA6 ChIP-seq in hiPSC-CMs 18 and our ERRγ ChIP-seq datasets.…”
Section: Resultsmentioning
confidence: 99%
“…The functions and gene targets of GATA6 are partially redundant with GATA4 35 37 . To determine whether ERRγ and GATA6 also shared targets, we conducted an intersection analysis with GATA6 ChIP-seq in hiPSC-CMs 18 and our ERRγ ChIP-seq datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, extensive studies have been conducted on the mechanisms by which H3K4 and H3K27 methylations impact heart development 11,14,15 . More recently, a critical role for histone H2B ubiquitylation (H2Bub) was demonstrated in cardiac development 16,17 . Knockdown of the Xenopus H2Bub E3 ligases, rnf20 (Ring finger protein 20) and rnf40 (Ring finger protein 40) 18 , beginning at the two-cell stage, influences cardiac looping and left-right (LR) asymmetry during early embryonic development 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results of an in vivo CRISPR/Cas9 genetic screen suggested that RNF20/40 is involved in cardiomyocyte (CM) maturation via H2Bub deposition 17 . Thus, RNF20 appears to be relevant to both CHD and CM maturation 16,19 . Nevertheless, the molecular function of RNF20 during temporal development of mammalian heart remains uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations